The Influence of Brand Image and Brand Trust on Purchase Intentions for Bottled Water, with Attitude as a Mediating Variable - Ike Ridaningsih; Novi Diah Wulandari; Regas Panji Pratomo (JURNAL ECONOMINA, 2026)
Changes in public consumption patterns toward bottled drinking water amid increasingly competitive brand rivalry have made consumer purchase intention an important aspect to investigate. This study explores the relationships among brand image, brand trust, and purchase intention, incorporating consumer attitude as a mediating variable. Data were obtained through a Likert-scale questionnaire administered to 220 respondents selected using purposive sampling. The findings indicate that brand image and brand trust positively contribute to the development of consumer attitude and purchase intention. Consumer attitude was also found to positively influence purchase intention and to partially mediate the relationships between brand image, brand trust, and purchase intention. These findings demonstrate that the Theory of Reasoned Action (TRA) remains relevant for explaining consumers’ purchase intentions for AQUA bottled drinking water products in Yogyakarta.